Social Policy in the Early Decentralization Era: Formulation and Politicization to the Local Public Health Insurance in Banyuwangi - Bayu Mitra A. Kusuma (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2018)
In the development of a country or a region, the quality of citizen’s health is very important. So that’s why, in order to improve the quality of citizen’s health, there needs a social policy action by the government, especially with the right decision making in its formulation process. In the local context, the Banyuwangi Public Health Services Insurance (JPKMB) Program is the answer to these problems, where the program offers free primary health service without charge for whole community levels. The main finding in this research is that in the decision making of the JPKMB Program, the decision-maker claims that they have done in-depth consideration and analysis using the rational approach model. But the facts on the research suggests that decision-makers tend to use an incremental approach model, where they make decisions quickly because it is affected by various limitations. This is due to health issues being politicized in terms of political campaigning purposes by one of the candidates who was competing in the local general elections of Banyuwangi Regency 2005. Consequently, after the candidate has been elected, the candidates should run the free health service program immediately, no matter what way. Its can be said that the decision making of the JPKMB Program is not going through a mature process.Dalam pembangunan suatu negara ataupun daerah, kualitas kesehatan masyarakat sangatlah penting. Oleh karena itu, untuk meningkatkan kualitas kesehatan masyarakat, dibutuhkan kebijakan sosial yang baik dari pemerintah, kususnya melalui pembuatan keputusan yang tepat dalam proses formulasinya. Pada tataran lokal, Program Jaminan Pelayanan Kesehatan Masyarakat Banyuwangi (JPKMB) adalah jawaban dari masalah tersebut, dimana dalam program tersebut disediakan pelayanan kesehatan gratis bagi seluruh lapisan masyarakat. Temuan utama dari penelitian ini adalah bahwa dalam pembuatan keputusan program JPKMB, pembuat keputusan mengklaim telah menggunakan pertimbangan dan analisis mendalam dengan model pendekatan rasional. Tapi pada faktanya peneliti lebih menemukan gejala bahwa pembuat keputusan cenderung menggunakan model inkremental, dimana mereka membuat keputusan dalam proses yang sangat cepat disebabkan berbagai keterbatasan. Dalam hal ini isu kesehatan telah dipolitisasi sebagai alat kampanye politik dari salah satu kandidat yang berkompetisi di Pilkada Banyuwangi 2005. Konsekuensinya setelah kandidat tersebut terpilih, pelayanan kesehatan gratis harus segera dilakukan, tidak peduli bagaimanapun caranya. Sehingga dapat dikatakan bahwa pembuatan keputusan program JPKMB tidaklah melalui proses yang matang.